Smoothness Morrey Spaces of regular distributions, and some unboundedness property. (July 2016) - Haroske, Dorothee D.; Moura, Susana D.; Skrzypczak, Leszek
Abstract: We study smoothness spaces of Morrey type on R n and characterise in detail when the spaces contain only regular distributions, i.e. when they can be embedded into L 1 loc . We also show that in all cases when it makes sense to study the growth envelope function of the proper smoothness Morrey spaces, it is always infinite.